Motivul muzicii şi al mării în proza lui Anton Holban - Teodorowicz, Justyna (Studia Romanica Posnaniensia, 2014)
The purpose of the present article is to discuss two literary motifs that can be traced throughout Anton Holban’s prose works: music and the sea. Holban, who wrote also music reviews for newspapers, had a genuine passion for music, which is reflected in his novels and short stories. Music appears in Holban’s literature as the highest form of artistic expression, and, at the same time, as a special and unique code used by lovers to communicate with each other, which isolates them from other people. Music seems to be more important than a relationship with a woman and even than literary creation. It may become an obsession. Listening to music in solitude gives the narrator an opportunity to explore his inner world and to be himself. The sea means much more than a landscape in Holban’s works. Like music, it has a symbolic dimension, being for the protagonists a source of extatic, almost mistic experience, as well as a witness to their deepest and most intimate feelings. From philosophical point of view, the sea means infinity, eternal movement and perfection.